2011
DOI: 10.12659/msm.881711
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of bilberry (Vaccinium myrtillus) against doxorubicin-induced oxidative cardiotoxicity in rats

Abstract: SummaryBackgroundDoxorubicin (DOX) is a commonly used chemotherapeutic agent. It is associated with serious dose-limiting cardiotoxicity, which is at least partly caused by generation of reactive oxygen species (ROS). Supplementations with bilberries were effective in reducing oxidative stress in many tissue injuries due their high content of antioxidants. The present study investigated the potential protective effect of bilberry extract against DOX-induced cardiotoxicity in rats.Material/MethodsRats were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…Similar results were obtained by previous studies [Richard et al, 2011;Colak et al, 2012;Warpe et al, 2015]. ECG revealed significant prolongation of QT interval in DOX-administered groups (II, III) as reported by Rahimi_Balaei et al [2010]; Ashour et al [2011] and Warpe et al [2015]; denoting delayed repolarization and a negative chronotropic effect [Gandhi et al, 2013] or metabolic and electrolyte abnormalities associated with developed heart failure [Hunter et al, 2008].…”
Section: Discussionsupporting
confidence: 88%
“…Similar results were obtained by previous studies [Richard et al, 2011;Colak et al, 2012;Warpe et al, 2015]. ECG revealed significant prolongation of QT interval in DOX-administered groups (II, III) as reported by Rahimi_Balaei et al [2010]; Ashour et al [2011] and Warpe et al [2015]; denoting delayed repolarization and a negative chronotropic effect [Gandhi et al, 2013] or metabolic and electrolyte abnormalities associated with developed heart failure [Hunter et al, 2008].…”
Section: Discussionsupporting
confidence: 88%
“…The reduced GSH brain content might be due to GSH consumption in DOX‐induced lipid peroxidation . The elevated TNF‐α and Casp‐3 by DOX treatment are in agreement with Refs.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the therapeutic effects of our protectants will start after 2 days of DOX injection, but in our study we stopped administration of protectants after 2 days of DOX injection due to the preventive study. Moreover, many published reports suggested 2 days’ regimen after DOX administration together with 5 or 7 days’ regimen before DOX administration as preventive study . The dose and duration of treatment were also based on pilot studies performed in our laboratory and showed the maximal effects for the selected doses (data not shown).…”
Section: Methodsmentioning
confidence: 99%